The Effect of House Ventilation and Floor Type on the Event of Measles in Jember District - Wahyudi, Gufron; Rahmawati, Lailatul (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Measles is a disease caused by the measles virus from the Paramyxovirus family, genus Morbilivirus. Measles is one of the communicable disease and one of the main causes of death in children under five. Jember Regency is one of the contributors to measles cases which is quite high, namely in 2015 there were 109 cases, in 2016 there were 266 cases. From 2017 to July there were 342 cases of measles. The incidence is very high compared to 2016. The purpose of the study was to analyze the effect of house ventilation and floor type on the incidence of measles in Jember Regency. The type of research is observational analytic using a Case Control approach which was carried out in the work area of ​​the Jember District Health Center where measles outbreaks occurred in 2017 namely Silo 2 Health Center, Rambi Puji Health Center, Arjasa Health Center, Panti Health Center, Sabrang Health Center, Jelbuk Health Center and Sukorambi Health Center. Samples taken were 100 respondents consisting of 50 case respondents and 50 control respondents. Research data sourced from primary and secondary data, research data collection using questionnaires and documentation studies. Processing and analyzing data using Logistics Regression test with a significance level of 5% (α=0.05). The results showed that house ventilation (p value = 0.005) had an effect on the incidence of measles in Jember Regency. Home ventilation has an effect on the incidence of measles because some respondents live in homes with inappropriate ventilation and most of them live in homes with ventilation 10% of the floor area.